Influence of Metal‐Alkyls on Early‐Stage Ethylene Polymerization over a Cr/SiO2 Phillips Catalyst: A Bulk Characterization and X‐ray Chemical Imaging Study. Issue 5 (9th December 2020) - Jongkind, Maarten K.; Meirer, Florian; Bossers, Koen W.; ten Have, Iris C.; Ohldag, Hendrik; Watts, Benjamin; van Kessel, Theo; Friederichs, Nic.; Weckhuysen, Bert M.
Abstract: The Cr/SiO2 Phillips catalyst has taken a central role in ethylene polymerization since its invention in 1953. The uniqueness of this catalyst is related to its ability to produce broad molecular weight distribution (MWD) PE materials as well as that no co‐catalysts are required to attain activity. Nonetheless, co‐catalysts in the form of metal‐alkyls can be added for scavenging poisons, enhancing catalyst activity, reducing the induction period, and tailoring polymer characteristics. The activation mechanism and related polymerization mechanism remain elusive, despite extensive industrial and academic research. Here, we show that by varying the type and amount of metal‐alkyl co‐catalyst, we can tailor polymer properties around a single Cr/SiO2 Phillips catalyst formulation. Furthermore, we show that these different polymer properties exist in the early stages of polymerization. We have used conventional polymer characterization techniques, such as size exclusion chromatography (SEC) and 13 C NMR, for studying the metal‐alkyl co‐catalyst effect on short‐chain branching (SCB), long‐chain branching (LCB) and molecular weight distribution (MWD) at the bulk scale. In addition, scanning transmission X‐ray microscopy (STXM) was used as a synchrotron technique to study the PE formation in the early stages: allowing us to investigate the produced type of early‐stage PE within one particle cross‐section with high energy resolution and nanometer scale spatial resolution. Abstract : Tailoring polymerization processes : The addition of the proper type and amount of co‐catalyst in a Cr/SiO2 Phillips‐type ethylene polymerization system tailors the molecular weight distribution and degree of short chain branching. We have now used scanning transmission X‐ray microscopy for investigating how these properties affect the polyethylene crystallinity in the early stages of ethylene polymerization.